1996
DOI: 10.1111/j.1432-1033.1996.00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Asp70 in the Peripheral Anionic Site of Human Butyrylcholinesterase

Abstract: The goal of this work was to determine what amino acids at the mouth of the active-site gorge are important for the function of human butyrylcholinesterase. Mutants D70G, Q119Y, G283D, A277W, A277H and A277W/G283D were expressed in human embryonal kidney cells and the secreted enzymes were assayed by steady-state kinetics. The result was that only one amino acid, D70 was found to be important for function. When D70 was mutated to G , the same mutation as in the naturally occurring atypical butyrylcholinesteras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
113
1
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(123 citation statements)
references
References 49 publications
8
113
1
1
Order By: Relevance
“…Moreover, our recent results indicate that, after initial interaction with Asp-70, positively charged substrates are correctly oriented to slide on to Trp-82, the actual ' anionic site ' [54]. Asp-70 is also involved in activation by excess substrate [10]. The present results show that Asp-70 is involved in the complex dependence of re-activation on pralidoxime iodide (2-PAM) concentration.…”
Section: Introductionmentioning
confidence: 50%
See 3 more Smart Citations
“…Moreover, our recent results indicate that, after initial interaction with Asp-70, positively charged substrates are correctly oriented to slide on to Trp-82, the actual ' anionic site ' [54]. Asp-70 is also involved in activation by excess substrate [10]. The present results show that Asp-70 is involved in the complex dependence of re-activation on pralidoxime iodide (2-PAM) concentration.…”
Section: Introductionmentioning
confidence: 50%
“…This residue is located at the rim of the active-site gorge, where it has been found to be a part of the peripheral anionic site (PAS) of BuChE [10]. Moreover, our recent results indicate that, after initial interaction with Asp-70, positively charged substrates are correctly oriented to slide on to Trp-82, the actual ' anionic site ' [54].…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Recent studies have suggested that a particular residue, D72 (D74 in mAChE and hAChE, D70 in hBChE), might contribute to the specificity of ChEs for cationic ligands by a trapping mechanism (Hosea et al, 1996;Masson et al, 1996). This residue is strategically placed near the top of the active-site gorge (Fig.…”
Section: Module I: a Surface Trap For Cationic Species Operating Via mentioning
confidence: 99%